Principles of Lower Extremity Deformity Correction in Children. Issue 6 (September 2017) - Mosca, Vincent S.
Abstract : Techniques change, but principles are forever. The techniques used to correct lower extremity deformities in children should be based on the principles of assessment and management of those deformities. This writing is a summation of the introductory lecture on deformity correction that highlights some of those principles.